The effect of project owners, plan-developers and characteristics of projects on airport building performance - Irfansyah, Reiza; Susetyo, Budi; ., Syafwandi (International Journal of Engineering and Technology, 2020)
The concept of Design and Build quickly becomes the preferred form of project completion. With this concept, it is possible for a project to be completed more quickly, with quality and costs according to plan. However, based on the results of research on construction projects in Jakarta, there are many that do not meet expectations.This study aims to determine the relationship of project owner factors, planner-builder factors, and project characteristics on airport design projects. Based on PLS SEM analysis of 65 respondents, it was found that the factor of the project owner has a positive but not significant effect on the performance of the Airport project, the builder planner has a negative but not significant effect on the performance of the Airport project, while the project characteristics factor has a positive and significant effect on project performance Airport.The results of this study provide confirmation and direction in the work of design projects in the future, especially for design projects at the airport.Â Â Â